FACTORS THAT INFLUENCE DISCIPLINE, ABILITY AND TEAMWORK ATTITUDES ON WORK CREATIVITY IN EMPLOYEES OF PT. KAYU SELASIHAN INDAH IN BONDOWOSO DISTRICT - Dewi, Gesty Rosita; Samsuryaningrum, Ira Puspitadewi; Winahyu, Pawestri (Dynamic Management Journal, 2025)
This research is based on the problems that occur at PT Kayu Selasihan Indah, namely the lack of work discipline that can have a negative impact on employee productivity in the company which can cause work to be slow, company goals not to be achieved, then it is difficult to achieve optimal results. The purpose of this research is to determine and analyze work discipline, skills and teamwork on work productivity of employees of PT Kayu Selasihan Indah in Bondowoso Regency. This research uses quantitative methods. Along with increasing global competition, companies are required to continue to improve the efficiency and effectiveness of their production. A deep understanding of the factors that influence work productivity is very important to achieve these goals. This research has a high urgency because it can contribute to the company in identifying areas that need to be improved to achieve higher productivity targets. In addition, the results of this study can also be a reference for other companies in the manufacturing sector, especially those who want to improve the performance of their employees. The data used in this research are primary data obtained through observation, questionnaires, interviews and secondary data through documentation. The population and sample of this study are employees of PT Kayu Selasihan Indah in Bondowoso Regency, totaling 110 employees. Bondowoso, totaling 110 employees. For data analysis, the author uses multiple linear regression analysis. Based on the results of hypothesis testing, it can be stated that attitude does not have a significant effect on employee work creativity, ability has a significant effect on employee work creativity, teamwork does not have a significant impact on employee work creativity.